Solvation consequences of polymer PVP with biological buffers MES, MOPS, and MOPSO in aqueous solutions. (December 2015) - Gupta, Bhupender S.; Chen, Bo-Ren; Lee, Ming-Jer
Graphical abstract: Highlights: Densities and viscosities data for aqueous solutions with PVP and/or buffer. The studied buffers include MES, MOPS, and MOPSO. DFT was used to estimate the binding energies of the (PVP + buffer) complexes. The viscosity data were correlated with the Jones–Dole equation. The investigated buffers behave as Kosmotropies. Abstract: Densities and viscosities were measured for the aqueous buffer (MES, MOPS, or MOPSO) solutions containing different concentrations of polyvinylpyrrolidone (PVP) (5, 10, 15, 20 and 30) mass% at temperatures from (298.15 to 318.15) K under atmospheric pressure. The DFT calculations were also performed and the binding energies of the possible (PVP + buffer) complexes were obtained. The experimental and computational results reveal the interactions of the PVP with the constituent compounds in the aqueous buffer solutions. Additionally we have explored the solvation behavior of the buffers by measuring the densities and the viscosities data of the aqueous buffer solutions from (0.0 to 1.0) mol · kg −1 at temperatures from (298.15 to 318.15) K. The viscosity results were correlated with the Jones–Dole equation. The correlated results confirmed that all the investigated buffers behave as Kosmotropes (structure makers).